Human papillomavirus vaccination at the national and provincial levels in China: a cost-effectiveness analysis using the PRIME model - Liangru Zhou; Baiyang Gu; Jian Wang; Guoxiang Liu; Xin Zhang (BMC, 2022)
Abstract Background Human papillomavirus (HPV) vaccines have been proven effective against cervical cancer. However, HPV vaccination is not included in the Chinese immunization program. This study aimed to assess the cost-effectiveness of incorporating different HPV vaccines into immunization programs at the Chinese national and provincial levels. Methods The Papillomavirus Rapid Interface for Modeling and Economics model was used to estimate the possible cost and social and economic benefits of adopting various HPV vaccination immunization strategies in 31 provinces in Mainland China in 2019. Demographic and regional economic data were obtained from the national and provincial Statistical Yearbook. The cost of vaccines was gathered from the centralized procurement information platform of all Chinese provinces. Treatment costs, epidemiological data, and other model parameters were obtained from published literature. The cost of vaccination, treatment costs saved, net costs, cases and deaths averted, life years saved, disability-adjusted life years (DALYs) prevented, and incremental cost-effectiveness ratios were predicted both provincially and nationally. Deterministic sensitivity analyses were used to explore model uncertainty. Results The net cost of vaccinating with the domestic bivalent HPV vaccine was the lowest. At the national level, after bivalent or quadrivalent HPV vaccination, the number of cases and deaths averted due to cervical cancer were 12,545 and 5109, respectively, whereas the 9-valent HPV vaccine averted 28,140 cases and 11,459 deaths. HPV vaccines were cost-effective at a national level (maximum cost US$ 18,165 per DALY gained.) compared to the 3 times GDP per capita (US$ 30,837). Bivalent HPV vaccines were cost-effective in all 31 provinces. Imported quadrivalent and 9-valent HPV vaccines were cost-effective in 29 provinces, except Heilongjiang and Gansu. The univariate sensitivity analysis showed that the results were robust when the model parameters were changed, and that the discount rate was the main factor affecting the baseline results. Conclusions This study provides evidence that the inclusion of HPV vaccination in the immunization program would be cost-effective at a national level and in most provinces. Provinces with a higher population have more prevented cases, deaths, and DALYs. The economics of HPV vaccination at the provincial level differs from that at the national level, and provinces with an inability to pay should seek help from state subsidies.